Paternal diet and exercise epigenetically program energy expenditure and glucose metabolism in mouse offspring - Koury, Michael (East Carolina University, 2014)
It is currently estimated that a third of Americans suffer from metabolic syndrome, which is an obesogenic disease shown to increase risk for developing type 2 diabetes (T2DM) by five-fold (Diabetes Care, 2012). The pervasiveness of obesity and T2DM is largely the result of unbalanced nutrition and lack of physical activity. Epidemiological investigations are now finding the detrimental effects of poor lifestyle choices, such as consuming a high-fat diet, have heritable consequences that persist transgenerationally by way of epigenetic modifications. The epigenome is yet another tier of genetic regulation, one that is capable of producing heritable changes in gene expression without altering the underlying sequence of nucleotides. In an effort to better understand the pathogenesis of these overly prevalent diseases (i.e. obesity and T2DM) researchers have now set their sights on faulty epigenetic machinery. To date, research has primarily focused on epigenetic modifications associated with maternal descent, mainly because of the significant influence had by lifestyle and the environment during 9-months in utero. Consequently, the roles of paternal lifestyle choices, like diet and activity, have not received adequate attention. Using a C57BL/6J mouse model we examined the transgenerational effects of a paternal high fat-diet and prolonged exercise on male offspring's susceptibility to glucose intolerance. Founder fathers (F₀) were randomly divided into three groups: control-diet fathers (CF) // high-fat fathers (FF); 60% of energy derived from fat // control-diet fathers with exercise wheel (EF). After 12 weeks of a high-fat diet (HFD) or free-wheel running F₀ males from each group were mated with control females. At 4 weeks of age their male offspring (F₁) were assigned to either a HFD or control diet (CD; 10% of energy derived from fat) for a duration of 12 weeks. Metabolic profiles were assessed via indirect calorimetry (i.e. metabolic cages), glucose tolerance testing (GTT), fasting plasma insulin, eMRI imaging (fat/lean body composition), as well as monitoring of developmental milestones. A comparison between cohorts of offspring on post-natal day 7 revealed a significantly lower mean birth weight in the HFD-father offspring (FFO); a factor shown in humans to be predictive of obesity and impaired glucose tolerance in adulthood (Bhargava et. al. 2004). Additionally, when challenged with a HFD only exercise father offspring (EFO) exhibited diabetic traits such as fasting hyperglycemia, fasting hyperinsulinemia, lower energy expenditure, as well as increased body weight and adiposity. To better understand the molecular mechanisms driving these observations quantitative real-time PCR was utilized to examine the methylation profile and gene expression within insulin sensitive tissues like the liver, pancreas, and gastrocnemius muscle. Data show intriguing differences in expression of several metabolic genes such as: Ogt, Oga, Pdk4, Glut4, Ptpn1, Igf2, H19, and FoxO1. Furthermore, with the exception of Glut4, methylation patterns in fathers were preserved within male offspring. These novel findings suggest that offspring have a phenotype that is epigenetically programmed to thrive under the same experimental conditions as their respective fathers.
Keywords: Physiology; Genetics; Public health; Diabetes; Energy; Epigenetics; Metabolism; Obesity; O-GlcNAc; Biology, Genetics; Biology, Physiology; Metabolic Syndrome X--metabolism; Diabetes Mellitus, Type 2--metabolism; Diet, High-Fat